2003
DOI: 10.1016/s0009-9236(03)90419-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of P‐glycoprotein in clinical effects of morphine, fentanyl and methadone

Abstract: Clinical Pharmacology & Therapeutics (2003) 73, P17–P17; doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…[11][12][13][14] It was reported that the inhibition of intestinal P-glycoprotein by oral administration of quinidine enhances the absorption and pharmacological effect of morphine in humans. 15) Oral administration of quinidine also elevated the antinociception of orally-administered morphine in rats. Grapefruit juice extracts cause a four-fold increase in the transport of [ 3 H]vinblastine, a P-glycoprotein substrate, from apical to basolateral sides across human intestinal Caco-2 cells.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…[11][12][13][14] It was reported that the inhibition of intestinal P-glycoprotein by oral administration of quinidine enhances the absorption and pharmacological effect of morphine in humans. 15) Oral administration of quinidine also elevated the antinociception of orally-administered morphine in rats. Grapefruit juice extracts cause a four-fold increase in the transport of [ 3 H]vinblastine, a P-glycoprotein substrate, from apical to basolateral sides across human intestinal Caco-2 cells.…”
Section: Resultsmentioning
confidence: 95%
“…[12][13][14] In humans, it has been reported that the absorption of morphine is regulated by intestinal P-glycoprotein. 15) Further, P-glycoprotein may be partially associated with morphine tolerance.…”
mentioning
confidence: 99%
“…P-glycoprotein mediates the efflux of morphine and affects the intestinal absorption of morphine in humans. 4) Thus the effects of morphine administration on P-glycoproteinmediated transport was characterized in Caco-2 cells using Since the accumulation was restored to the control level by the addition of cyclosporin A, it is suggested that the decrease in [ 3 H]vincristine accumulation is due to the stimulatory effects on P-glycoprotein-mediated efflux. The accumulation of rhodamine123 was also decreased after culture with morphine, and the efflux of rhodamine123 from Caco-2 cells was significantly increased after culture with morphine.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, P-glycoprotein (ABCB1, an MDR1 gene product), a drug resistance-related transporter, affects the intestinal absorption of morphine in humans and the distribution of morphine in the brain in mice and rats. [4][5][6][7][8] Aquilante et al reported that repeated morphine administration caused a two-fold increase in the level of P-glycoprotein in the rat brain associated with a decrease in the antinociceptive effects. 9) King et al also reported that an antisense-oligo against mdr1a suppressed the development of antinociceptive tolerance to intracerebroventricularly administered morphine.…”
mentioning
confidence: 99%
See 1 more Smart Citation